Teaching Strategies in Physical Education: A Literature Review of Practices in the United States, China, and Nigeria - Donaire, Ester R. (Future Science / FSH-PH Publications, 2024)
This study offered a literature of Physical Education (PE) strategies employed in the United States, China, and Nigeria, shedding light on diverse approaches influenced by unique cultural, societal, and governmental factors. In the United States, a flexible and inclusive PE curriculum prioritizes student engagement and lifelong physical activity through diverse activities and personalized instruction. Conversely, China's structured PE programs emphasize discipline, physical fitness, and early talent identification, supported by robust government policies. Nigeria's PE teaching strategies integrate cultural relevance, community involvement, and adaptive resource utilization to promote physical activity despite resource constraints. Through cross-cultural learning and recommendations for government investment, teacher training, community engagement, and health education integration, stakeholders can enhance PE programs globally, fostering physical activity, sports participation, and overall well-being among students.